PS-P14-6: SALTCON FESTIVAL IN KYOTO 2022 BY SALT REDUCTION PROMOTION TEAM OF JAPANESE SOCIETY OF HYPERTENSION PRACTITIONERS SUBCOMMITTEE. (January 2023) - Hatta, Tsuguru; Noma, Gentoku; Takase, Hiroyuki; Ozono, Ryoji; Tsuge, Toshinao; Minowa, Hitoshi; Ando, Katsuyuki; Narumi, Jun; Aoki, Soichiro; Yoshiikawa, Hiroyuki; Mizuta, Einosuke; Kudo, Hiroshi; et al.
Abstract : Background: In September 2011, the United Nations and WHO, based on an article published in the Lancet, proposed five actions that the entire world should take to combat noncommunicable diseases (NCDs). In order of priority, they are: 1. Tobacco Control > 2. Salt Reduction > 3. Improved Diets and Physical Activity > 4. Essential Drugs and Technologies. However, looking back over the past decade, while Tobacco Control has made progress, Salt Reduction still has a ways to go. In fact, a Systematic Analysis published in the Lancet in 2019 places "salt" at the top of the list of dietary factors that negatively impact life expectancy and health span. Therefore, the Festival has identified "Salt Reduction" as a global issue to be addressed in the next decade, and will implement programs to accelerate Salt Reduction efforts. *SOLCON: Abbreviated term for Salt Consious (visualize) and Salt Control (adjust). Purpose: Accelerate Salt Reduction efforts (Involving people who have never had anything to do with salt before) (1) Overview (three events will be held, each described in detail below) (2) Forums for organizations (sharing Population Approach), held on the web (3) Markets targeting individuals (practice of Individual Approach), holding Real Public lectures for individuals, held on the web Meeting Date: (1) Forum: Thursday, November 24, 2022, 12:00 - 17:00 (2) Market: Sunday, November 13, 2022, 10:00–15:00 (3) Public Lecture: Saturday, November 19, 2022, 16:00–18:00 Reduce salt! is not enough to reach the health-unconcerned population, and to reduce salt consumption, we have planned an event like the Japanese version of CASH (the National Council on Salt and Health), a collaboration of industry, government, and academia. We hope that this project will be a catalyst for reducing salt consumption in Japan.